QOL-25. END-OF-LIFE EXPERIENCES OF CHILDREN WITH BRAIN TUMORS: PERSPECTIVES FROM A PANEL DISCUSSION. Issue 2 (22nd June 2018) - Brock, Katharine; Connelly, Erin; Jackson, Brian; Wrubel, David; Mazewski, Claire
Abstract: BACKGROUND: Brain tumors (BTs) have the highest mortality rate of all pediatric neoplasms. Patients with BTs have distinct constellations of symptoms including fatigue, headaches, seizures, cognitive impairment, loss of consciousness, speech impairments, swallowing difficulties, paralysis, incontinence, steroid-induced side effects, pain secondary to immobility, psychological effects, and changes to interpersonal interactions. Caring for children and young adults with BTs through the end-of-life (EOL) poses unique challenges for parents, caregivers, and providers alike. PROPOSAL: Using case examples of pediatric patients with high grade malignant tumors with poor prognoses such as diffuse intrinsic pontine glioma, high grade gliomas and recurrent medulloblastoma, we will explore the differing trajectories, decision-making points, and EOL experiences of children and the families who care for them. We will highlight cases where similar clinical scenarios have differing courses and outcomes. An expert panel including parents and clinicians in neuro-oncology, neuro-surgery, developmental therapeutics, palliative care, nursing, and ethics will provide various viewpoints, exhibiting opportunities for collaboration in care planning and debating points of contention. The panel's discussions will focus on (1) shared decision making and ethical challenges around use of chemotherapy, radiation, steroid therapy, and surgical interventions such as resections and shunt placement, (2) early phase trial enrollment (both at one's home institution or at another center), (3) advance care planning and the role of palliative care and/or hospice, (4) the use of complementary and alternative therapies and (5) the EOL experience for children and families choosing differing paths. Audience members will be allotted time to question the panel.